Weather Sensitivity to Clothing Expenditure in Two Climate Zones in South Korea - Oh, Jungmi; Son, Jun-Hyeok (International Journal of Costume and Fashion, 2025)
The fashion industry must adapt to increasingly unpredictable weather events caused by climate change. Accurate demand forecasting is essential for achieving Sustainable Development Goals. This study examines the influence of key weather factors on seasonal clothing expenditures in Seoul and Busan, South Korea utilizing both weather and economic data from 2010 to 2022. Hierarchical regression analysis is used to examine the impact of these weather factors on clothing expenditures for each season. The findings indicate that clothing expenditures vary significantly by season. The clothing sentiment index has a positive impact on expenditures across all seasons. While clothing expenditure in spring and winter shows only minor sensitivity to weather changes, temperature fluctuations in summer and fall have a more significant impact. Consumers in Seoul are sensitive to variations in relative humidity during summer, while those in Busan show no significant relationship between relative humidity and their purchasing behavior. Additionally, clothing expenditure in Seoul is more sensitive to changes in the wet bulb globe temperature compared to those in Busan. This study carries important practical implications, offering the potential for more accurate demand forecasting and improved business decision-making within the fashion industry KCI Citation Count: 0